Escape from the `lost decades?' Governance challenges in Argentina, Brazil, Colombia, Mexico, and Venezuela - Edward L. Knudsen (Global Policy, 2023)
Much of Latin America has experienced a renewed `lost decade', failing to substantially expand quality of life since the late 2000s. While the outcomes of governance performance across the largest countries – including Brazil, Venezuela, Mexico, Colombia, and Argentina – have discrete causes, common themes like internal conflict, corruption, and overreliance on natural resources plague the entire region. Put more generally, the inability to turn democratic accountability into a state mechanism able to deliver economic growth and public goods in a sustainable manner is a liability affecting all five countries. To explore the difficulties that the large Latin American countries have faced in the twenty-first century, this article examines results from the 2022 Berggruen Governance Index, and then presents three key issues facing the region: insufficient state capacity, flirtations with authoritarianism, and economic inequality and inflation. While the challenges remain substantial, increased regional integration may offer one way out of the predicament.
Keywords: 320